A REVIEW ON CHROMATOGRAPHY TECHNIQUES - Luxminarayan, Lodha; Sharma, Neha; Viswas, Amit; Viswas, Amit; Khinchi, Dr.M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Chromatography techniques like HPLC, Gas chromatography, Paper chromatography, TLC, etc and their working principle and applications for various samples. Different physical and chemical properties of wide ranges of the test samples to be seprated by the specific chromatographic methods selected which enumerate the seprations, identifications and analysis with optimum output for particular samples. This review deals with discussion of the conventional as well as sophisticated of various efforts for particular samples. The study signifies the appliance of chromatography at various stages of drug discovery and development